La castración química ¿una solución para reducir la violación y abuso sexual de menores? - Gonzales, Gustavo F. (2022)
Recently, in our country, chemical castration has called the attention of politicians once again as a possible measure to reduce rape and sexual abuse of childs. Chemical castration, a therapy mediated by pharmacological treatment, has been used for 50 years in some countries against those sentenced for sexual crimes. Chemical castration reduces androgen levels but it is reversible after the end of the therapy. Androgens, particularly testosterone, can modulate almost all aspects of sexual behavior thanks to the wide distribution of their receptors throughout the brain. Therefore, it is expected that androgen reduction through chemical castration can reverse atypical and aggressive sexual behaviors that are exacerbated in paraphilias, such as pedophilia. The most common medications used in chemical castration to treat paraphilic disorders are synthetic steroid analogs, gonadotropin-releasing hormone (GnRH) antagonists, and GnRH analogs (agonists). Each drug uses a different mechanism of action and has different effects on the physiological and psychological characteristics of paraphilic disorders. In general, the amount and quality of research with these drugs is limited and not enough to support their use. In addition, there are various ethical, legal and logistical complications that should be considered before applying chemical castration. Rather, mental health promotion programs should be developed for people with paraphilia where they can be treated anonymously to avoid criminal behavior.